2017
DOI: 10.1111/anec.12512
|View full text |Cite
|
Sign up to set email alerts
|

Catecholaminergic polymorphic ventricular tachycardia, an update

Abstract: Catecholaminergic polymorphic ventricular tachycardia is a rare devastating lethal inherited disorder or sporadic cardiac ion channelopathy characterized by unexplained syncopal episodes, and/or sudden cardiac death (SCD), aborted SCD (ASCD), or sudden cardiac arrest (SCA) observed in children, adolescents, and young adults without structural heart disease, consequence of adrenergically mediated arrhythmias: exercise-induced, by acute emotional stress, atrial pacing, or β-stimulant infusion, even when the elec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
74
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(76 citation statements)
references
References 50 publications
0
74
0
2
Order By: Relevance
“…ß‐blockers form the cornerstone of management of CPVT; however, 30% of patients demonstrate inadequate response . Among β‐blockers, nadolol is more effective than β 1 ‐selective agents in suppressing arrhythmias in patients with CPVT .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…ß‐blockers form the cornerstone of management of CPVT; however, 30% of patients demonstrate inadequate response . Among β‐blockers, nadolol is more effective than β 1 ‐selective agents in suppressing arrhythmias in patients with CPVT .…”
Section: Discussionmentioning
confidence: 99%
“…Catecholaminergic polymorphic ventricular tachycardia (CPVT) is a rare (prevalence: 1/10,000) channelopathy characterized by premature ventricular contractions (PVCs), and monomorphic, bidirectional, or polymorphic ventricular tachycardia (VT). Arrhythmias are often triggered by exercise, acute emotion, or stress and most patients with CPVT have structurally normal hearts and normal resting electrocardiograms (ECG) . In addition to VT, atrial arrhythmias such as atrial fibrillation (AF), atrial flutter, and atrial abnormalities such as sinus node dysfunction and atrial standstill have been reported .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations